PERAN MUHAFIZH DAN MOTIVASI MENGHAFAL AL-QUR’AN TERHADAP PRESTASI MTQ SANTRI NON MUKIM - Siti Sarah; Ahmad Hawasi (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
This research aims to analyze the role of muhâfizh in educating non-mukim students to become hafidz of the Qur'an and also to find out how much influence muhâfizh 's motivation has on the MTQ achievements of nonmukim students at the study at KH Abdurrahman Tangerang City. This research is a descriptive qualitative research, namely research that aims to apply a social phenomenon or an event. The research was conducted directly at the study of KH. Abdurrahman Makmun which is located on Jl. H. Usan, Rt 05 Rw 03, Belendung sub-district, Benda sub-district, Tangerang city, Banten province. The research was carried out on 15 to 24 June 2021. Related to the theoretical basis in this research, it is about learning motivation and achievement. The results of this study are 1) The role of Muhâfizh on the MTQ achievements of non-mukim students in the KH study. Abdurrahman Makmun, consists of several actions, namely: Providing guidance to the students, both in the activities of depositing memorization and coaching when the students want to take part in MTQ, paying attention to the students, instilling discipline, providing examples, giving advice and providing motivation. 2) Regarding the motivation for the MTQ achievements of non-mukim students at the KH study. There are two types of Abdurrahman Makmun, namely: First, intrinsic motivation, the reason why the students want to memorize and maintain memorization so that the memorization fluency becomes good, namely: wanting to be a person who is able to keep his word, want to make parents proud, want to explore science. knowledge of the Qur'an, want to undergo the law (fardhu kifayah) memorize the Qur'an. Second, extrinsic motivation, the factors that encourage students to memorize come from outside, namely: family motivation, including parents, environmental motivation, including teachers, friends/friends, and the community, MTQ motivation